Step-by-step explanation:
Let's assume that
[tex]P(n)\ =\ 2^{2n-1}+1[/tex] is divisible by 3.
for n= 1
[tex]P(1)\ =\ 2^{2.(1)-1}+1[/tex]
= 3
Hence, P(1) is true for n=1
for n=2
[tex]P(2)\ =\ 2^{2.(2)-1}+1[/tex]
= 9, which is divisible by 3.
As we can see, P(n) is also true for n= 2.
Let's say P(n) is true for n = k
So,
[tex]P(k)\ =\ 2^{2k-1}+1[/tex] is divisible by 3.
[tex]=>\ P(k+1)\ =\ 2^{2(k+1)-1}+1[/tex]
[tex]=\ 2^{2k+1}+1[/tex]
For P(n) should be true, the difference of P(k+1) and P(k) must will have divisible by 3.
So,
[tex]P(k+1)-P(k)\ =\ 2^{2k+1}+1-(2^{2k-1}+1)[/tex]
[tex]=\ 2^{2k-1}(2^2-1)[/tex]
[tex]=\ 3\times 2^{2k-1}[/tex]
as P(k+1)-P(k) is divisible by 3.
As a result, P(n) is true for all n>1.